2017
DOI: 10.3892/ol.2017.6710
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid augments the radiosensitivity of cancer cells through perturbing S- and M-phase cyclins and p21CIP1 expression

Abstract: Abstract. Radiotherapy and adjuvant chemotherapy have become the standard treatments for multiple types of cancer. Although cancer cells are usually sensitive to radiotherapy, metastasis and local failure still occur mainly due to developed resistance to radiotherapy. Thus, it is critical to improve therapeutics for cancer treatment. The present study demonstrated that third-generation bisphosphonate zoledronic acid (ZOL), even at a low concentration, augments the radiosensitivity of cancer cells exposed to io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…In addition, treatment with carbon-ion beam irradiation combined with ZOL increased the number of cells in the G2/M phase, compared to the case for treatment with carbon-ion beam irradiation and ZOL alone, suggesting that the combination treatment significantly attenuated cell cycle progression. These findings are partially consistent with previous reports stating that ZOL augments the X-ray or γ-ray radiosensitivity of fibrosarcoma and nasopharyngeal carcinoma cells [22][23][24][25][26], indicating that ZOL not only enhances low LET photon beam radiosensitivity, but also high LET carbon-ion beam radiosensitivity in OSA cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, treatment with carbon-ion beam irradiation combined with ZOL increased the number of cells in the G2/M phase, compared to the case for treatment with carbon-ion beam irradiation and ZOL alone, suggesting that the combination treatment significantly attenuated cell cycle progression. These findings are partially consistent with previous reports stating that ZOL augments the X-ray or γ-ray radiosensitivity of fibrosarcoma and nasopharyngeal carcinoma cells [22][23][24][25][26], indicating that ZOL not only enhances low LET photon beam radiosensitivity, but also high LET carbon-ion beam radiosensitivity in OSA cells.…”
Section: Discussionsupporting
confidence: 93%
“…These data suggest that ZOL acts as an inhibitor of both the PI3K/Akt-and MAPK-signaling pathways, thereby enhancing the effects of carbon-ion beam irradiation on OSA cells. These results support the findings of recent studies that the combination treatment with ZOL increased cytotoxic effects via suppression of the Pi3K/Akt and MAPK signaling pathways [24,26,41,42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Vascular endothelial growth factor (VEGF) is an inducer of angiogenesis due to its highly specific mitogen for endothelial cells [17]. However, ZA, one of most widely used BPs, reduces the mRNA and protein expressions of VEGF and decreases serum levels of VEGF and other cytokines, such as interleukin-17, involved in angiogenesis [18]. In PDRN treatment for diabetes and burns, VEGF is produced by the actions on adenosis A2 receptors [19], which may contribute to increased angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…They achieved control of the local disease in 94% of patients followed for an average of 19.2 months. As a result, the combination of Zoledronate and SBRT in the treatment of vertebral metastasis was well tolerated and reported that it reduced the rate of vertebral collapse, effectively reduced pain, and provided good local tumor control without late neurological side effects (10). Lu et al examined the combination of radiofrequency ablation, 125I-seed, zoledronic acid or radiotherapy in patients with spinal metastasis percutaneous vertebroplasty.…”
Section: Introductionmentioning
confidence: 99%